Mughal warfare : Indian frontiers and highroads to empire, 1500-1700 - Gommans, Jos J. L. (Warfare and history., 2003)
Based on a vast range of primary sources from Europe and India, this thorough study explores the wider geo-political, cultural and institutional context of the Mughal military.